2020
DOI: 10.1186/s12894-020-00618-1
|View full text |Cite
|
Sign up to set email alerts
|

Axitinib as a third or further line of treatment in renal cancer: a single institution experience

Abstract: Background: Kidney cancer is a lethal neoplasm that affects several thousands of people every year. Renal cell carcinoma (RCC) is the most common histologic type. Recent developments in the therapeutic approach include antiangiogenic targeted approaches and Immunotherapy. Thus, the therapeutic algorithm of RCC patients and the survival outcomes have changed dramatically. Methods: Herein we present a retrospective study of the patients treated in our Department with an antiangiogenic agent-Axitinib, a tyrosine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The AXIS study compared axitinib and sorafenib and found that axitinib led to significantly higher PFS in secondline therapy (6.7 months vs. 4.7 months) (Rini et al 2011). Experience from a single institution in Greece indicated that axitinib is effective beyond second-line treatment (Tsironis et al 2020). A study in Italy showed a PFS of 7.14 months for axitinib after sunitinib (Facchini et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The AXIS study compared axitinib and sorafenib and found that axitinib led to significantly higher PFS in secondline therapy (6.7 months vs. 4.7 months) (Rini et al 2011). Experience from a single institution in Greece indicated that axitinib is effective beyond second-line treatment (Tsironis et al 2020). A study in Italy showed a PFS of 7.14 months for axitinib after sunitinib (Facchini et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 78 , 79 Potent inhibitors of VEGFRs 1–3 such as axitinib and bevacizumab are being used in the treatment of renal cell carcinoma and epithelial ovarian, fallopian tube, or primary peritoneal cancer respectively. 80 , 81 As aberrant activation and regulation of these receptors have been extensively observed in development of cSCC. The major RTK inhibitors have been summarized in Table 1 and the use of these inhibitors might be an efficient strategy for the treatment of cSCC.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Regarding kinase inhibitors, axitinib has been used in numerous investigations for CRC, a retrospective study [40] where it was used as third or fourth line of treatment in patients with advanced kidney cancer, raised a mean PFS of 6.27 months and OS of 19.2 months. For metastatic patients treated with axitinib [41], 5.7 months of PFS were reported, with 15.4 OS.…”
Section: Jiridmentioning
confidence: 99%
“…Regarding kinase inhibitors, axitinib referred by other cite [40] caused grade 3 and higher toxicity in 31% of patients and the dose had to be reduced in 5 (22%) cases and the drug had to be suspended in 3 patients (13%). Other authors [41] reported grade 3 or 4 treatment-related AEs in 79% and 26% of patients.…”
Section: Jiridmentioning
confidence: 99%